Rapid Colorimetric Assay for Detection of Listeria monocytogenes in Food Samples Using LAMP Formation of DNA Concatemers and Gold Nanoparticle-DNA Probe Complex - Wachiralurpan, Sirirat; Sriyapai, Thayat; Areekit, Supatra; Sriyapai, Pichapak; Augkarawaritsawong, Suphitcha; Santiwatanakul, Somchai; Chansiri, Kosum (Frontiers in Chemistry, 2018)
ABSTRACT Listeria monocytogenes is a major foodborne pathogen of global health concern. Herein, the rapid diagnosis of L. monocytogenes has been achieved using loop-mediated isothermal amplification (LAMP) based on the phosphatidylcholine-phospholipase C gene (plcB). Colorimetric detection was then performed through the formation of DNA concatemers and a gold nanoparticle/DNA probe complex (GNP/DNA probe). The overall detection process was accomplished within approximately 1 h with no need for complicated equipment. The limits of detection for L. monocytogenes in the forms of purified genomic DNA and pure culture were 800 fg and 2.82 CFU mL-1, respectively. No cross reactions were observed from closely related bacteria species. The LAMP-GNP/DNA probe assay was applied to the detection of 200 raw chicken meat samples and compared to routine standard methods. The data revealed that the specificity, sensitivity and accuracy were 100%, 90.20% and 97.50%, respectively. The present assay was 100% in conformity with LAMP-agarose gel electrophoresis assay. Five samples that were negative by both assays appeared to have the pathogen at below the level of detection. The assay can be applied as a rapid direct screening method for L. monocytogenes.